Analisis Strategi Pembentukan Karakter dan Kreatifitas Guru Kepada Siswa di RA Maghfirah (International Forum of Researchers and Lecturers, 2023)
Character education is a system of instilling character values in school members which includes components of knowledge, intelligence or will, and actions to implement these values. Character education is a deliberate effort to build good character based on core virtues that are objectively good for individuals and society. The research method used is a qualitative method involving data collection techniques in the form of observation and interviews. The data collected was then analyzed inductively, namely by identifying patterns, themes and concepts that emerged from the data. The purpose of this literature is to determine teacher strategies and creativity as an effort to improve character education for students. The results of the research show that the improvement efforts made by teachers at RA Maghfirah have been very good, teachers always accustom children to what they have been taught. The strategy used by teacher RA Maghfirah in forming children's character is related to habitual activities. The implication of this research is that it is hoped that teachers can use various models, methods and learning media to increase students' creative thinking.